RETRACTED : Pengembangan instrumen asesmen literasi kimia pilihan ganda materi asam basa - Eli Khusmawardani; Muntholib Muntholib; Yudhi Utomo (Universitas Negeri Malang, 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) to article entitle